1987
DOI: 10.1159/000100748
|View full text |Cite
|
Sign up to set email alerts
|

Five-and-a-Half Years' Experience with Percutaneous Retrogasserian Glycerol Rhizotomy in Treatment of Trigeminal Neuralgia

Abstract: The results of treating trigeminal neuralgia with percutaneous retrogang-lionic glycerol rhizotomy in 319 patients from an overall series of 394 patients with 459 operations carried out over a period of 5½years are reported. Idiopathic trigeminal neuralgia was the diagnosis in 252 patients. 34 patients had trigeminal neuralgia associated with multiple sclerosis. The remaining 33 patients suffered from symptomatic trigeminal neuralgia or atypical facial pain. 230 patients (91.3%) with idiopathic trigeminal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
1
10
1
5
Order By: Relevance
“…Herpes may therefore be a sign of properly performed rhizolysis. In our series, the frequency was low compared to some other studies [2,5,6,8,9]. However, most eruptions appeared after the patient had been dis-charged from hospital, and the eruptions were often mild and short-lasting, which may explain why patients may have forgotten this complication when follow-up was performed.…”
Section: Discussioncontrasting
confidence: 54%
“…Herpes may therefore be a sign of properly performed rhizolysis. In our series, the frequency was low compared to some other studies [2,5,6,8,9]. However, most eruptions appeared after the patient had been dis-charged from hospital, and the eruptions were often mild and short-lasting, which may explain why patients may have forgotten this complication when follow-up was performed.…”
Section: Discussioncontrasting
confidence: 54%
“…Cheng et al [3] reported that pain recurred in 9 of 16 patients after alcohol blocks, in 2 of 7 patients after radiofrequency rhizotomy and in 2 of 6 patients after PRGR. Dieckmann et al [18] reported that PRGR for patients with idiopathic trigeminal neuralgia was associated with initial pain relief in 91% but a recurrence rate of 11% within the first 2 years. Steiger [19] reported 122 patients who underwent PRGR.…”
Section: Discussionmentioning
confidence: 99%
“…3,18,40,46 Among patients undergoing primary PRGR for classic TN, rates of initial pain relief of between 79% and 92% have been reported, with 50% of patients pain free after 4 years. 7,17,32,35 Among patients with recurrent TN after PRGR who undergo GKRS, repeat PRGR has been reported to be associated with faster pain relief than repeat GKRS (median time to pain relief < 24 hours), but shorter duration of pain relief, greater perioperative morbidity, and a higher failure rate than GKRS. 31,32 One patient in our series underwent PRGR 17 months following the third GKRS.…”
Section: The Effect Of Other Surgical Procedures On Outcomesmentioning
confidence: 99%